(3OjhGf GdCOHs - (3ESMGb Hf EHQGgje Hf GdMSjf GdaGQGHqj, CHh EHQGgje, J (B350 (3g` s
(3ChdgG (B:s
(3GeG HYO aEf Gddg bOQ ddCTjGA bOQgG haVd HYVgG Ydi HYV hcGf ef aVGFdg JaVjd GdeUWai Ydjg GdSdGe s
(3BNQgG (B:s
(3CdG CNHQce HGdfaS GdhGQOI GddeMI GdjSjQI JeJ GdcdeGJ GdJhGHY hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B293s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B774s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs